YouTube and Arabic Vocabulary Acquisition in Muslim Families: A Psychosociolinguistic Perspective - Ahmad Yanif Firdaus; Muhammad Thohir; Sovia Fahraini; Maziyyatul Muslimah; Muhammad Alfa Choirul Murtadho (UIN Syekh Wasil Kediri, Indonesia, 2025)
The rapid development of social media and the internet has raised concerns about its impact on children's language acquisition processes, especially in the family context. In Muslim families, the use of digital media such as YouTube is often part of children's daily lives. This study aims to reveal how the digital environment, especially YouTube social media, plays a role in children's Arabic vocabulary acquisition in Muslim families. This study uses a qualitative approach with a case study method. The subjects of the study consisted of several Muslim families who actively use social media, especially YouTube, in their children's daily activities. Data collection was carried out through direct observation and in-depth interviews with parents and children, to explore digital media consumption practices and language interactions that occur. The results of the study show several main findings. The digital environment plays a role in enriching children's Arabic vocabulary through audiovisual content. The active involvement of parents in directing and accompanying the use of social media greatly determines the effectiveness of language acquisition. Vocabulary acquisition patterns are formed through exposure to Arabic content with Islamic nuances. There are supporting factors (educational content, controlled duration, mentoring) and inhibiting factors (irrelevant content, passive consumption) from the digital environment. The language acquisition process occurs informally but significantly in the family environment. Social digital environments such as YouTube have great potential in supporting informal Arabic language learning at home. In a psycho-sociolinguistic perspective, this study emphasizes the importance of the role of Islamic families in filtering and mentoring children's digital media consumption. Therefore, the use of digital media must be done consciously and structured in the context of language education. Perkembangan pesat media sosial dan internet telah menimbulkan kekhawatiran mengenai dampaknya terhadap proses pemerolehan bahasa anak, khususnya dalam konteks keluarga. Dalam keluarga Muslim, penggunaan media digital seperti YouTube kerap menjadi bagian dari kehidupan sehari-hari anak. Penelitian ini bertujuan untuk mengungkap bagaimana lingkungan digital, khususnya media sosial YouTube, berperan dalam pemerolehan kosakata bahasa Arab pada anak-anak dalam keluarga Muslim. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek penelitian terdiri atas beberapa keluarga Muslim yang secara aktif menggunakan media sosial, terutama YouTube, dalam aktivitas keseharian anak-anak mereka. Pengumpulan data dilakukan melalui observasi langsung dan wawancara mendalam dengan orang tua dan anak, guna menggali praktik konsumsi media digital serta interaksi kebahasaan yang terjadi. Hasil penelitian menunjukkan beberapa temuan utama. Lingkungan digital berperan dalam memperkaya kosakata bahasa Arab anak melalui konten audiovisual. Keterlibatan aktif orang tua dalam mengarahkan dan mendampingi penggunaan media sosial sangat menentukan efektivitas pemerolehan bahasa. Pola pemerolehan kosakata terbentuk melalui paparan konten berbahasa Arab yang bernuansa Islami. Terdapat faktor pendukung (konten edukatif, durasi penggunaan yang terkontrol, serta pendampingan) dan faktor penghambat (konten yang tidak relevan dan konsumsi yang bersifat pasif) yang berasal dari lingkungan digital. Proses pemerolehan bahasa berlangsung secara informal namun signifikan dalam lingkungan keluarga. Lingkungan digital sosial seperti YouTube memiliki potensi besar dalam mendukung pembelajaran bahasa Arab secara informal di rumah. Dari perspektif psiko-sosiolinguistik, penelitian ini menegaskan pentingnya peran keluarga Muslim dalam menyaring dan mendampingi konsumsi media digital anak. Oleh karena itu, penggunaan media digital perlu dilakukan secara sadar dan terstruktur dalam konteks pendidikan bahasa.